Adolescents’ reports of parental objectification of others’ bodies are associated with their body image and eating behaviors - Carolanne Tanguay; Camille Lavoie; Geneviève Lavigne; Noémie Carbonneau (BMC Psychology)
Abstract Background This study examined the extent to which adolescents’ perceptions of their parents’ sexually objectifying behaviors toward other people’s bodies and fat talk comments about individuals with higher weight are associated with adolescents’ own body image and eating behaviors. Both positive (body esteem and intuitive eating) and negative (body dissatisfaction and bulimia symptoms) dimensions of these outcomes were assessed. Methods Participants were 434 teenagers (350 girls, 56 boys, and 28 gender-diverse) aged 14 to 17 years (M = 15.72, SD = 1.00), recruited through social media advertisements. To assess their parents’ propensity for body objectification, the adolescents completed an adapted version of the Interpersonal Sexual Objectification Scale and a fat talk scale. They also completed questionnaires assessing their body image and eating behaviors. Results Structural equation modeling revealed that fathers’ (but not mothers’) sexually objectifying behaviors toward other people’s bodies were associated with adolescents’ body image outcomes, specifically greater body dissatisfaction and lower body esteem. Fathers’ and mothers’ sexually objectifying behaviors toward other people’s bodies were also linked to adolescents’ eating behaviors, including more bulimia symptoms and less intuitive eating. Moreover, mothers’ (but not fathers’) fat talk about individuals with higher weight was associated with adolescents’ body image outcomes (i.e., greater body dissatisfaction and lower body esteem), but not with their eating behaviors. Conclusions These findings suggest that how parents comment on and treat other people’s bodies may relate to their adolescent child’s body image concerns and eating behaviors, with distinct patterns emerging for fathers and mothers.